Factors Influencing Lesbianism Among Female Football Players in West Java: A Sociocultural Analysis - Primadi, Zahra Naqiyyah; Fitri, Mustika; Umaran, Unun; Apriady, Hilmy (Journal of Sport Science and Fitness, 2024)
This study aims to explore the factors influencing the sexual orientation of lesbian female football players in West Java and its implications for their personal and professional lives. Using a descriptive quantitative approach, data were collected through a Likert-scale questionnaire covering three main categories: background, reasons for attraction, and future expectations. The sample consisted of 37 respondents selected through purposive sampling. The analysis revealed that the environment was the dominant factor influencing players' sexual orientation, with the highest average score of 3.38. The nature of football, which fosters close interaction among female players, was the primary reason for attraction (average 2.6). However, respondents also faced challenges related to insecurity in openly expressing their sexual identity in the football environment (average 1.78). Future expectations indicated a tendency to conform to social norms, such as marrying a male partner for societal acceptance and a more stable life (average 3.49), while support for the legalization of same-sex marriage was low (average 1.46–1.68). Simple regression analysis showed a significant influence between background and reasons for attraction (p < 0.05), whereas Pearson correlation analysis revealed a positive relationship between reasons for attraction and future expectations (r = 0.350). This study highlights the need for an inclusive sports environment to reduce stigma and discrimination against players with diverse sexual orientations.